Clinical chemistry : principles, techniques, and correlations - Bishop, Michael L.; Fody, Edward P.; Siclen, Carleen Van; Mistler, James March; Moy, Michelle (Burlington, MA : Jones & Bartlett Learning, 2023)
"Medical Lab Science students need a strong foundation in applied chemistry need to learn and demonstrate mastery of the required knowledge, skills and competencies as specified by certifying bodies and accreditation organizations to be prepared for certification and employment as a professional medical assistant. ear explanations that balance analytic principles, techniques, and correlation of results with coverage of disease states. For over 30 years and 8 editions Bishop has gained the reputation in the market as the trusted resource written by Clinical Lab Scientists specifically for CLS students. Many of the leading books on the market are adapted from general chemistry textbooks, while Bishop sets itself apart from the competition by its logical organization reorganize the chapter order to reflect clinical chemistry flow in most courses today. Individual chapter content will be based on the ASCLS Entry Level Curriculum. A map of how the textbook correlates to the ASCLS curriculum will be provided as an instructor resource. Bishop not only demonstrates the how of clinical testing, but also the what, why, and when of testing correlations to help students develop the knowledge and interpretive and analytic skills they will need in their future careers"--
Includes bibliographical references and index.
Keywords: Clinical chemistry